Improving Primary Health Care Delivery in Nigeria : Evidence from Four States - World Bank (World Bank, 2012)
This study aims mainly at understanding the performance of primary health care (PHC) providers in four Nigerian states and the variables driving this performance. The study is primarily based on quantitative surveys at the level of primary health care facilities, health care personnel, and households in their vicinity. These surveys were implemented in four states: Bauchi, Cross River, Kaduna, and Lagos. This study represents the second phase of the Nigeria Health, Nutrition, and Population Country Status Report (CSR). The first phase aimed at analyzing the health situation of the poor and how the health system was performing in terms of meeting their needs. This first phase identified PHC as the weakest chain in the entire health sector and the level of care the poor use the most. This second phase of the CSR is therefore focused on the analysis of the delivery of PHC services. In contrast to the first phase, this study is mainly based on primary data, data collected through facility, health personnel, and household surveys. This study follows a similar methodology used by a facility survey implemented in Kogi and Lagos in 2002 (Das Gupta, Gauri, and Khemani, 2003). However, this study is focused in the collection of information not previously available, such as detailed roles and responsibilities of the LGA and states and community perceptions of PHC services.